Perempuan Bali dalam Ketidakadilan Gender: Tinjauan Perspektif Psikologi Sosial dan Gender - Putu Wahyuni Mahaputri (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Patriarchy is a social system that positions men as the main, central authority in social society. This patriarchal culture is still common in all aspects of life. This study aims to analyze the existing patriarchy in customs and traditions using a social psychology concept approach, namely social construction, gender roles and toxic masculinity. This research method uses a literature study with the concept of cultural psychology. The results of this study show that the customs and traditions that exist in Bali are still thick with the influence of patriarchal culture. This can have an impact on women, such as experiencing anxiety and stress. The conclusion of this research is the social construction that forms the existence of patriarchy in customs and traditions.